Biosimilar formulations of gonadotropins in a central Italian region: use patterns and time trends. (30th September 2020) - Rosa, A; Belleudi, V; Addis, A; Ciardulli, A; Pacchiarotti, A; Davoli, M; Kirchmayer, U
Abstract: Background: Gonadotropins (Gonas) are hormones that play a central role in the follicular growth of women but also useful in male infertility. Gonas used for infertility treatment in women are available as urinary extracts or recombinants. In 2015, the first biosimilar of follitropin alfa was authorised. Objectives: We aimed to evaluate use patterns, temporal and spatial variations of Gonas biosimilar formulations in an central Italian region. Methods: From administrative healthcare databases of Lazio region, we extracted prescriptions that have occurred over the years 2015-2019. Gona's use was grouped as treatment with urinary (u) and recombinant (r). Special focus was made on biosimilar r-Gona. Use patterns were investigated with respect to characteristics of the patients treated, time trends, differences among local health units and type of prescribing physician. Results: For the study period, we retrieved 136, 333 Gona dispensations for 22, 325 patients. The 10, 927 r-Gona biosimilar dispensations (8.01% of all claims, of which 99.43% Bemfola®, and 0.57% Ovaleap®), were mostly referred to women, aged 18-45 years, (87.11% of all patients). Median age was 37 years for women, 38 for men. Since its authorisation, biosimilar r-Gona steadily gained market from 2015 (0, 4% of claims) to 2017 (22, 7%) followed by a decrease in 2019 (4, 3%). Biosimilars claims are more frequent in treating men (10, 8%) than women (6, 1%). Most biosimilar prescriptions were issued by general practitioners (86.4%), followed by specialists (10.2%) and others. Biosimilar use patterns varied between different local health units (IQR 3.2%-8, 5%). Conclusions: In clinical pratice, r-Gona biosimilar dispensation, 8, 8% of Gonas. are mostly prescribed from general practitioners and are proportionately more targeted at men than women. Further investigation is needed. Key messages: More and more men and women are using artificial insemination techniques; it is important to monitor fertility drug use patterns. In times of savings for the economic system, the use of the biosimilar drugs is of increasing interest.